Factor influencing real estate buying behaviour during COVID-19 (case study: Petaling Jaya, Selangor) / Mohd Shafiq Abd Mutallib and Hafiszah Ismail - Abd Mutallib, Mohd Shafiq; Ismail, Hafiszah (College of Built Environment, 2023)
There has been an increasing rate in the property market over the years. However, because of Covid-19, the price of house property began to fall, despite home-buyers being unable to afford to purchase a home during this time period because most of them were losing their jobs.